Influencia de la innovación abierta, la flexibilidad estratégica y la gestión de riesgos corporativos en la ventaja competitiva: Análisis en el sector hotelero portugués; Influence of open innovation, strategic flexibility, and corporate risk management on competitive advantagesanalysis in the portuguese hotel sector - Jorge de Andrés Sánchez; Eugenio Musiello-Neto; Orlando Manuel Martins Marques de Lima Rua; Mario Arias-Oliva (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2023)
– The objective of the article is to carry out a review of the subject of composite indicators, especially that related to the methodological process associated with their construction, detailing and discussing the various steps linked to said process, using the construction of the Competitive Potential Index Departmental (IPCD) as a reference., an indicator that measures the competitive potential of the Departments (administrative regions) in Uruguay, in order to show a specific case and the options that were taken in its construction, without going into the detailed explanation of said indicator. The main reflection that should be highlighted is the need for transparency in the construction of the index. That is, the strength of the composite index and its usefulness in the future will depend directly on the quality of the information and the justification provided for each of the decisions made by the researcher (or research team) in charge of building the index.This paper analyses the effects of open innovation (OI), organizational strategy and the existence of a corporate risk management (CRM) strategy on competitive advantage (CA) in cost, service and product in the Portuguese hotel sector. This paper uses a survey over 251 CEOs of Portuguese small and medium-sized enterprises (SMEs) hotels and applies two complementary statistical methods: partial least squares regression and quantile regression. It can be stated that both OI and the degree of dynamism and flexibility of the organizational structure and CRM are relevant to explain the different types of competitive advantage. However, the results show that the importance of the incidence of the different explanatory factors considered is different depending on the type of competitive advantage that we are analysing and the relevance of disaggregating those associated with AI (inbound and outbound) and organizational strategy (dynamic of the environment, internal organizational flexibility and innovative strategic position). Thus, the CRM variable is the fundamental variable in the explanation of the competitive advantage in cost, while the incidence of inbound OI is especially relevant in the CA in service and product. Within organizational strategy, the factor that most clearly affects competitive advantage is the strategic position with respect to innovation.
Keywords: C21; M15; O32; 330; Inbound open innovation; outbound open innovation; competitive advantage; hotel industry; quantile regression